Analysis of Corner Effect of Diaphragm Wall of Special-Shaped Foundation Pit in Complex Stratum - Li, Yaodong; Wang, Chongxiao; Sun, Yang; Wang, Ruicai; Shao, Guojian; Yu, Jie (Frontiers in Earth Science, 2022)
The number of special-shaped foundation pits is increasing fast because of the continuous utilization of underground spaces in urban areas. Beased on the deep foundation pit of Maluan North Station of Xiamen Metro Line 2 in Xiamen, China the deformation characteristics of supporting structure of special-shaped foundation pit are researched by field observation and numerical simulation. Meanwhile, the depth of the concrete supports and steel supports is considered respectively. The results show that the lateral deformation of diaphragm wall at the corner of pit shows obvious corner effect, the maximum lateral displacement of the long-side diaphragm wall is slightly larger than the short-side. Changing the position of the second layer of steel support has almost no effect on the lateral deformation of the corner diaphragm wall. Changing the position of the second layer of concrete support has a greater impact on the lateral displacement of the diaphragm wall, but the path of the maximum lateral displacement of the diaphragm wall and the depth of the point of maximum lateral displacement remain unchanged.